PENINGKATAN FASILITAS KANTOR DESA MELALUI PEMASANGAN PLAFON PVC DI DESA RIMO, KECAMATAN GUNUNG MERIAH, KABUPATEN ACEH SINGKIL - Hanova, Yudha; Sari, Kartika Indah; Nusa, Ahmad Bima; Subeki, Tryswan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The village office plays a vital role as the center of administrative services for the local community, thus requiring adequate facilities to support the smooth operation of public services. In Rimo Village, Gunung Meriah Subdistrict, Aceh Singkil Regency, the poor and damaged condition of the village office ceiling has become one of the main obstacles affecting both the comfort and aesthetics of the workspace. Through this community service initiative, the installation of ceilings made from PVC (Polyvinyl Chloride) was carried out as an effort to improve the office facilities. The implementation method began with a site survey, followed by design planning, selection of optimal materials, and the final installation of the PVC ceiling at the village office. The results of the activity indicate that the installation of PVC ceilings has had a positive impact on improving both the comfort and functionality of the village office workspace.